Determinasi Evaluasi Kinerja dan Loyalitas Terhadap Promosi Jabatan (Studi Kasus Salah Satu Perusahaan di Pangkep Sulawesi Selatan) - Hastuti Mulang (AkMen JURNAL ILMIAH, 2022)
This study aimed to determine how employee loyalty and performance evaluation influence career advancement decisions. The quantitative method with non-probability sampling and a purposive sampling strategy is employed for the investigation. Using the Slovin equation, a sample of 85 employees from PT Prima Karya Manunggal, Pangkep, South Sulawesi was obtained. By providing questionnaires to responders, data was gathered. Using a five-point Likert scale, fifteen indications generated from three different factors were measured. The utilized analytical method is multiple linear regression, which has undergone a data feasibility test and a classical assumption test. The results indicated that the variables of performance evaluation and employee loyalty had a favorable and statistically significant impact on career advancement. In limited testing, it has been determined that employee loyalty has a significant impact on promotion.